Clinical Outcomes and Immunologic Characteristics of Coronavirus Disease 2019 in People With Human Immunodeficiency Virus. (30th June 2020) - Ho, Hsi-en; Peluso, Michael J; Margus, Colton; Matias Lopes, Joao Pedro; He, Chen; Gaisa, Michael M; Osorio, Georgina; Aberg, Judith A; Mullen, Michael P
Abstract: We performed a retrospective study of coronavirus disease 2019 (COVID-19) in people with human immunodeficiency virus (PWH). PWH with COVID-19 demonstrated severe lymphopenia and decreased CD4 + T cell counts. Levels of inflammatory markers, including C-reactive protein, fibrinogen, D-dimer, interleukin 6, interleukin 8, and tumor necrosis factor α were commonly elevated. In all, 19 of 72 hospitalized individuals (26.4%) died and 53 (73.6%) recovered. PWH who died had higher levels of inflammatory markers and more severe lymphopenia than those who recovered. These findings suggest that PWH remain at risk for severe manifestations of COVID-19 despite antiretroviral therapy and that those with increased markers of inflammation and immune dysregulation are at risk for worse outcomes. Abstract : In this retrospective review of people with HIV and severe acute respiratory syndrome coronavirus 2 coinfection, COVID-19 was characterized by severe lymphopenia and elevated levels of inflammatory markers that were associated with adverse outcomes. Severe COVID-19 occurred despite suppressive antiretroviral therapy in this cohort.